Improving Educational Equity through the Smart Indonesia Card for College: Policy Implementation and Challenges - Novitasari, Shinta; Siswanto, Djoko; Ambarwati, Arie (Universitas Teuku Umar, 2025)
The Smart Indonesia Card for College (KIP-Kuliah) is a government program designed to promote educational equity by providing financial assistance to economically disadvantaged students pursuing higher education. This study examines the implementation of KIP-Kuliah at Nahdlatul Ulama University Sidoarjo (UNUSIDA) and Maarif Hasyim Latif University (UMAHA), focusing on policy communication, resource availability, administrative structure, and implementation challenges. Using a qualitative descriptive approach and George Edward III's policy implementation model, this research finds that KIP-Kuliah has successfully supported underprivileged students by reducing financial barriers. However, several challenges remain, including limited communication between funding institutions and universities regarding quotas and disbursement procedures, a lack of budget for program socialization, and inefficiencies in the verification and selection process, which are still being conducted manually. Despite these obstacles, the program benefits from strong parental support, adequate campus resources, and effective coordination between KIP-Kuliah administrators and financial offices. The study concludes that while KIP-Kuliah effectively enhances educational access, improving communication channels, increasing socialization efforts, and implementing an expert system for scholarship selection are necessary to optimize program execution